Experimental Study of Mechanical and Durability Characteristics of Bio-Mineralized Concrete: A Microstructure Analysis - R. Porselvan; T. S. Lakshmi; Muniyandi Tholkapiyan (Журнал інженерних наук)
Concrete primarily composed of cement is essential for construction but contributes to significant natural resource depletion and environmental concerns. To address this, substituting cement with pozzolanic materials (e.g., fly ash and micro silica) was explored to enhance sustainability while maintaining strength. However, challenges remain in optimizing the durability and self-healing capacity of concrete. This study aims to study the impact of bacterial concrete using Bacillus subtilis on strength and durability properties. The main focus of bio-mineralization was to improve the mechanical performance and sustainability of building materials. Concrete specimens were subjected to curing for 7, 14, and 28 days. As a result, compressive strength, flexural strength, split tensile strength, and durability parameters (i.e., water permeability and chloride penetration) were evaluated. Microstructural analysis through energy dispersion spectra and field-emitting scanning electron microscopy provided insights into the calcite precipitation mechanism within the concrete pores, aiding in densification and strength enhancement. The results demonstrated that bacterial infusion significantly improved strength at all cell concentrations compared to control specimens. Moreover, the bacterial concrete exhibited enhanced self-healing properties, as observed through reduced permeability and chloride penetration. This study highlights the potential of bacterial concrete to enhance structural performance and environmental sustainability, offering a viable solution for both improving durability and reducing the carbon footprint of concrete construction.